"and My soul shall abhor you": Implicit processing of social disgust. (1st January 2021) - Berger, Uri; Anaki, David
Abstract: Disgust has a social component in which others are perceived as more disgusting than the self. Key characteristics of this social component were examined in six experiments. Experiment 1 established the social disgust Implicit Association Test (SD-IAT) applicability for assessing social disgust. Results revealed a congruency effect, in which participants implicitly associated other-race strangers with disgusting stimuli. Experiment 2 explored whether the SD-IAT effect is the result of familiarity. Unfamiliar in-group and out-group members were presented in the IAT. Results were identical to those of Experiment 1. Experiments 3 (using intergroup stimuli) and 4 (using interpersonal stimuli) investigated whether the SD-IAT congruency effect stems from disgust directed at others or from self-liking. Results showed a larger congruency effect for social disgust than for self-liking. Experiments 5 and 6 investigated whether SD stems from an association between the non-self and either disgust or negative valence. Findings showed a larger SD-IAT congruency effect for disgust. The combined results delineate the core aspects of SD and show that it is a heterogeneous phenomenon, based on relative social categories, in which the non-self is perceived as disgusting. Highlights: Disgust social aspect causes others to be perceived as more disgusting than the self. Key characteristics of social disgust were examined in six IAT experiments. Social disgust was found to be a heterogeneous phenomenon. Social disgust is not a by-product of self-enhancement, or positive self-esteem. Social disgust is not in-group bias; others are disgusting and negative.